Lessons learned from the science of caring: Extending the reach of psychosocial oncology: The International Psycho‐Oncology Society 2016 Sutherland Award Lecture. Issue 6 (9th March 2017) - Bultz, Barry D.
Abstract: In medicine, referral to a medical oncology specialty is based on recent history, physical examination, pathology, surgery reports, imaging, blood work, and the patient's vital signs. By contrast, referral to a psychosocial specialist has typically been based on the patients expressed request for psychosocial support or the health care team's observation of the patient's limited adjustment or poor coping with the diagnosis, treatment, or end‐of‐life distress. These observations are usually based on clinical acumen not on metrics. In psychosocial oncology, by committing to the science of caring and relying on the use of standardized tools to screen for distress, the multidisciplinary cancer care team assess, communicate, and intervene on what is measured. That is, health care providers can begin to address the patients' identified concerns. Branding distress as the 6th vital sign and incorporating screening for distress into standard cancer practice can be an effective strategy to challenging the resistance in implementation of psychosocial oncology in cancer care institutions. Accreditation agencies are endorsing the need to assess patient distress and better manage symptoms of distress as part of routine and standardized patient care. While many international organizations and societies support the importance of screening, implementing screening for distress still has a long way to go to be operationalized in many cancer care programs. Screening for distress when implemented does, however, create an opportunity for psychosocial oncology to extend its reach into cancer care programs and institutions.